2013
DOI: 10.1097/jfn.0b013e31827a1e9d
|View full text |Cite
|
Sign up to set email alerts
|

At a Crossroads

Abstract: The exponential increase in the number of women parolees and probationers in the last decade has made women the most rapidly growing group of offenders in the United States. The purpose of this descriptive, qualitative study is to understand the unique gendered experiences of homeless female ex-offenders, in the context of healthcare needs, types of health services sought, and gaps in order to help them achieve a smooth transition post prison release. Focus group qualitative methodology was utilized to engage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Our previous, qualitative research (Nyamathi et al, 2016; Salem, Nyamathi, Idemundia, et al, 2013) and extensive community-based work have informed the development of the DBT-CM intervention and engaged collaboration between CHWs and nurses during reentry to help homeless female offenders more successfully transition into the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous, qualitative research (Nyamathi et al, 2016; Salem, Nyamathi, Idemundia, et al, 2013) and extensive community-based work have informed the development of the DBT-CM intervention and engaged collaboration between CHWs and nurses during reentry to help homeless female offenders more successfully transition into the community.…”
Section: Discussionmentioning
confidence: 99%
“…Among women, recidivism associated with drug-related violations is greater than those of male offenders (32% vs. 21%) (Leukefeld et al, 2009). Few gender-sensitive programs address drug and alcohol use and recidivism behaviors (Salem, Nyamathi, Idemundia, Slaughter, & Ames, 2013), which necessitates obtaining information about how to effectively address the unique needs of the homeless female exoffender following release.…”
mentioning
confidence: 99%
“…During the reentry period, many women faced challenges seeking employment due to a history of incarceration. Previous research have also validated the desire for women to be employed (Salem et al, 2013); however, employment opportunities were limited for those with a history of incarceration. For some women, lack of adequate financial resources resulted in relapse due to the need for “quick money.” Future research necessitates connecting formerly incarcerated women with a network of providers which can provide opportunities for long term employment and continued training.…”
Section: Discussionmentioning
confidence: 99%
“…As the male parolee study was being implemented, female residents of the RDT questioned why they were not able to participate in the male study. Focus group sessions with several female residents in a RDT program (Salem, Nyamathi, Idemundia, Slaughter, & Ames, 2013) led the way to on-going discussions with the administrative community at the RDT about the design of a Female Ex-Offender study.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional health care barriers for homeless populations may include lack of transportation and long wait times (Salem, Nyamathi, Idemundia, Slaughter, & Ames, 2013), along with being uninsured; in fact, 59.5% of a homeless population did not have health insurance coverage (Baggett et al, 2010). In one study of MSM, the majority reported received care from a physician (59%) and community/public health clinic (20%) and 22% reported not having any health insurance coverage (Kipke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%